2004
DOI: 10.1016/j.neuron.2004.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Structure, Protein Dynamics, and Synaptic Function of SAP97 Controlled by L27 Domain Interactions

Abstract: Single-particle electron microscopy (EM) combined with biochemical measurements revealed the molecular shape of SAP97 and a monomer-dimer transition that depended on the N-terminal L27 domain. Overexpression of SAP97 drove GluR1 to synapses, potentiated AMPA receptor (AMPAR) excitatory postsynaptic currents (EPSCs), and occluded LTP. Synaptic potentiation and GluR1 delivery were dissociable by L27 domain mutants that inhibit multimerization of SAP97. Loss of potentiation was correlated with faster turnover of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

38
274
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(315 citation statements)
references
References 63 publications
38
274
3
Order By: Relevance
“…However, we found that the exchange of PSD-95-GFP was slow at the PSD (Fig. S4 B-D), consistent with previous work (22,25,26,31). Preincubation of neurons with jasplakinolide or latrunculin for 15 min did not affect the low rate or extent of PSD-95-GFP fluorescence recovery (Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…However, we found that the exchange of PSD-95-GFP was slow at the PSD (Fig. S4 B-D), consistent with previous work (22,25,26,31). Preincubation of neurons with jasplakinolide or latrunculin for 15 min did not affect the low rate or extent of PSD-95-GFP fluorescence recovery (Fig.…”
Section: Resultssupporting
confidence: 92%
“…5. It will be important to assess whether these or other oligomeric interactions of PSD proteins (22,39,40) confer stability to the complex as a whole or to subsets of proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In γ-8-knockout mice, hippocampal synaptic transmission and plasticity are reduced (Rouach et al, 2005). Overexpression of the MAGUK PSD95 increases AMPAR-mediated transmission (Beique and Andrade, 2003;Ehrlich and Malinow, 2004;Nakagawa et al, 2004;Schnell et al, 2002), and PSD93 PSD95 double-knockout mice show a severe impairment in fast excitatory transmission (Elias et al, 2006). GRIP, NSF and PICK1 interact directly with the cytoplasmic tail of the GluR2 subunit of AMPARs (Kim et al, 2001;Luthi et al, 1999;Setou et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The PSD-95-like subfamily of neuronal MAGUKs (PSD-MAGUKs) includes PSD-93, SAP102, and SAP97 (15)(16)(17). Comparative studies emphasize the remarkable similarities among PSD-MAGUKs in terms of protein-protein interactions (18,19) and overlapping functions in synaptic trafficking of AMPARs at mature synapses (20)(21)(22)(23)(24). On the other hand, the temporal coincidence of the early postnatal developmental switch from NR2B-to NR2A-NMDARs with the switch from SAP102 to PSD-95 expression raises the possibility that the two processes are related (25).…”
mentioning
confidence: 99%